PENATALAKSANAAN FISIOTERAPI PADA KONDISIFROZEN SHOULDER DEKSTRA DENGAN MODALITASTRANCUTANEUS ELECTRICAL NERVE STIMULATION,SHORT WAVE DIATHERMY,DAN MOBILISASI WITH MOVEMENT - Fara Aufilana Rahmatika; Ade Irma Nahdliyyah (SINERGI : Jurnal Riset Ilmiah, 2026)
Frozen Shoulder or Adhesive Capsulitis is a musculoskeletal disorder characterized by pain and limited range of motion of the shoulder joint due to the occurrence of glenohumeral capsule contracture. This condition can lead to a decrease in muscle strength as well as disruption of daily functional activities. This study aims to determine the effectiveness of Transcutaneous Electrical Nerve Stimulation (TENS), Short Wave Diathermy (SWD), and Mobilization With Movement (MWM) in patients with Frozen Shoulder Dextra. The research method used was an analytical descriptive case study with the provision of physiotherapy interventions as many as 4 times of therapy. Evaluation was carried out on the patient's pain, muscle spasms, range of joint motion, muscle strength, and functional activity. The results showed a decrease in pain, reduced deltoid muscle spasm, increased range of motion of the shoulder joint, increased muscle strength, and increased functional activity ability of patients. It can be concluded that the combination of TENS, SWD, and MWM is effective in helping the recovery of shoulder function in patients with Frozen Shoulder Dextra. These findings show that physiotherapy has an important role in improving patients' quality of life through improvements in movement and body function.